Educational assessment : - Wright, Robert J. (Sage, 2008)
The book includes sections on the history of testing in America, the meaning and quality of test scores, classroom testing, aptitude testing, and national and international standards for testing, including a history of legislature in America relating to educational assessment. Each section closes with discussion questions